Scoring System Assessment of Cephalic Vein Access for Device Implantation - Jane Taleski; Poposka, Lidija; Janusevsi, Filip; Pocesta, Bekim; Boskov, Vladimir; Boyle G, Noel (MediaSphere Medical, LLC, 2018)
The purpose of this study was to explore the usability of the cephalic vein (CV) for cardiac implantable electronic device (CIED) lead access by applying a scoring system to assess the venous anatomy. This prospective, single-center study included 100 consecutive patients who underwent CIED implantation within a period of one year. Contrast-enhanced venography images were obtained for every patient, focused on the CV, “T-junction,” and the subclavian/ axillary veins (SV/AVs). Though careful examination of the images, an angle, valves, diameter, noncollateral (AVDnC) score was constructed and used to aid in choosing a CV or SV/AV access approach; in all cases, however, the preferred approach was CV independent of the AVDnC score result obtained. Upon use of the scoring system, the majority of patients (54%) had type A score result ( 3), indicating a favorable anatomy for CV access. In 48 of these patients, the CV was used for the implantation of at least one lead. The remaining 46 (46%) patients had type B score result ( 2). In 41 patients from this group, SV/AV access was used for lead implantation and, in five patients, CV access was used. The number of leads introduced through the CV was associated with larger score and the operator’s experience. In conclusion, in more than 50% of patients, at least one lead could be introduced through the CV. The scoring system used herein can simplify the choice between CV and SV/AV access and could eventually increase the efficiency and safety of the procedure, especially when less experienced implanters are involved.
Keywords: axillary vein; cephalic vein; device implantation; score assessment; subclavian vein